A physical-analytical model for a real-time local grip estimation of tyre rubber in sliding contact with road asperities. (July 2014) - Farroni, Flavio; Russo, Michele; Russo, Riccardo; Timpone, Francesco
This paper deals with the frictional behaviour of a tyre tread elementary volume in sliding contact with road asperities. Friction is assumed to be composed of two main components: adhesion and deforming hysteresis. The target, which was fixed in collaboration with a motorsport racing team and with a tyre-manufacturing company, is to provide an estimation of local grip for online analyses and real-time simulations and to evaluate and predict adhesive and hysteretic frictional contributions arising at the interface between the tyre tread and the road. A way to approximate the asperities, based on rugosimetric analyses on a macroscale and a microscale, was introduced. The adhesive component of friction was estimated by means of a new approach based on two different models found in the literature, whose parameters were identified thanks to a wide experimental investigation previously carried out. The hysteretic component of friction was estimated by means of an energy balance taking into account the viscoelastic behaviour of rubber (which was characterized by means of appropriate dynamic mechanical analysis tests) and the internal stress–strain distribution (which was due to indentations of the road). The model results are finally shown and discussed, and the validation experimental procedure is described. The correct reproduction of the friction phenomenology and the model prediction capabilities are highlighted, making particular reference to the grip variability due to changes in the working conditions.